A Bánság roma népességének néhány jellemzője - Kókai Sándor (2015)
The Bánság played a prominent role in the history of the roma population in Hungary, on one side it served as a continuous migration path for gypsies, on the other hand it helped the development of their language dialects. The stereotypes related to the roma population in the 19th century have not proven to be relevant, the ratio of the Bánság’s roma population had not risen above the national average by that time. The historical society of Hungary was unprepared for the roma migration wave during dualism, the ad hoc solutions did not lead to lasting results. The Bánság’s roma population in 1893 was 26,897 people, and amongst the 804 settlements of the region only 575 settlements were registered as populated by romas. The region’s roma population growth was three-fold between 1857–93, that exceeded the value in the historical Hungary and Transylvania too. At the end of the 19th century the spatial distribution of Bánság’s roma was closely correlated with the migration paths and regional territorial distribution of raw materials for handicraft products they manufacture. Despite the significant migration paths took place from east to west, as well as from villages to towns in the last century, the main settlement areas of Bánság’ gypsies today are the same as registered in 1893. Today, these areas have significant roma population, whose faster integration is mainly the result of moderate demographic differences. In order to reach smooth assimilation this population needs policy which encourage education, employment, public security, which provide opportunities for the roma population in the socio-economic ascent.